Material computation—4D timber construction: Towards building-scale hygroscopic actuated, self-constructing timber surfaces. (March 2016) - Wood, Dylan Marx; Correa, David; Krieg, Oliver David; Menges, Achim
The implementation of active and responsive materials in architecture and construction allows for the replacement of digitally controlled mechanisms with material-based systems that can be designed and programmed with the capacity to compute and execute a behavioral response. The programming of such systems with increasingly specific response requires a material-driven computational design and fabrication strategy. This research presents techniques and technologies for significantly upscaling hygroscopically actuated timber-based systems for use as self-constructing building surfaces. The timber's integrated hygroscopic characteristics combined with computational design techniques and existing digital fabrication methods allow for a designed processing and reassembly of discrete wood elements into large-scale multi element bilayer surfaces. This material assembly methodology enables the design and control of the encoded direction and magnitude of humidity-actuated responsive curvature at an expanded scale. Design, simulation, and material assembly tests are presented together with formal and functional configurations that incorporate self-constructing and self-rigidizing surface strategies. The presented research and prototypes initiate a shift toward a large-scale, self-construction methodology.